Effet De La Technologie, Du Cultivar Et De La Durée De Conservation Sur La Stabilité Et La Qualité Du Lait De Soja (Glycine maxima) - Paul A. F. Houssou; Pélagie B. Agbobatinkpo; Nestor R. Adjovi Ahoyo; Patrice Y. Adegbola; Abel B. Hotegni; Clovis M. Todohoue; Valère Dansou; Rachidatou Sikirou; Adonaï Gad da Matha Sant’anna; Patrice L. Sewade (European Scientific Journal, ESJ, 2018)
Three technologies named D (wet dehulled soybeans seeds), B (boiled soybean seeds before dehulling) and T (roasted soybean seeds before dehulling) for stabilized soymilk production were tested with TGX (large grain size) and Jupiter (small grain size) cultivars. Production yields, sensory, physicochemical and microbiological characteristics of produced milks were determined over a period of 3 months. . The bottled milk was sterilized at a temperature of 115°C under a pressure of 0.7 bar for one hour. The milks were stored at temperature storage place 27°C (for 3 months). The milk yield for technology D is 90.87 % for the jupiter and 92.01 % for the TGX. These yields are higher than the other technologies. Whatever the technology, the TGX cultivar gives a better yield 92.01 %. Sensory analysis revealed that the milk produced with technology D and jupiter cultivar is more appreciated by the 77 % panelist. This milk has a pH of 7.14 at the day of production and decreases to 6.83 after 3 months of storage. Protein, fat and Dry Soluble Matter (DSM) content decreased after storage by 4.30 to 4.13 %, 1.7 to 1.2 % and from 11.68 to 10.28 °Brix respectively. The viscosity was 1.24 cp at the beginning and 1.38 cp after storage. After 3 months of storage, the milk is stable and its microbiological quality complies with accepted standards in relation to spores, coliforms, yeasts and molds.